IMPLEMENTATION FRAMEWORK FOR BUSINESS PROCESS AUTOMATION: AN INTEGRATED APPROACH TO ORGANIZATIONAL TRANSFORMATION - Ranadheer Suram (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a comprehensive framework for implementing business process automation, emphasizing organizational integration and sustainable adoption. The article examines the critical factors that influence successful automation implementation, including strategic planning, tool selection, cross-functional collaboration, and cultural adaptation. Through systematic analysis of implementation strategies, this article proposes an integrated approach that addresses the challenges of data integrity, scalability, and system integration while maintaining organizational effectiveness. The article emphasizes the importance of clear, objective definitions, employee training, and continuous monitoring through key performance indicators. Furthermore, the article explores how organizations can foster a culture of adaptation through structured feedback mechanisms and iterative improvement cycles. The findings suggest that successful automation implementation requires a balanced approach between technical excellence and organizational change management, supported by strong cross-functional collaboration between business units and IT teams. This article contributes to the growing body of knowledge on business process automation by providing actionable insights for practitioners while establishing a theoretical framework for sustainable implementation strategies.